2017
DOI: 10.1371/journal.pone.0189289
|View full text |Cite
|
Sign up to set email alerts
|

Treatment following myocardial infarction in patients with schizophrenia

Abstract: BackgroundA correlation between excess mortality from myocardial infarctions (MI) and schizophrenia has already been established. What remains unclear is whether the initial communication between the treating doctor and the corresponding patient contributes to this excess mortality.AimThe aim of this study is to investigate whether a patient with schizophrenia receives the same offers for examination and treatment following a MI compared to a psychiatric healthy control (PHC).MethodsThis cohort study includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
5
18
0
3
Order By: Relevance
“…Despite the progression and availability of coronary procedures and the increasing awareness of the discrepancies in these populations, the significant difference in the use of CAG, PCI, and CABG between the populations has remained constant for the last 20 years. This is in accordance with previous research that has found fewer coronary procedures in the population with schizophrenia as compared to the general population, which has been ascribed to a combination of patient denial of symptoms, patient decline of treatment offers, and fewer offers made by the doctor [6].…”
Section: Time Trends In Proceduressupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the progression and availability of coronary procedures and the increasing awareness of the discrepancies in these populations, the significant difference in the use of CAG, PCI, and CABG between the populations has remained constant for the last 20 years. This is in accordance with previous research that has found fewer coronary procedures in the population with schizophrenia as compared to the general population, which has been ascribed to a combination of patient denial of symptoms, patient decline of treatment offers, and fewer offers made by the doctor [6].…”
Section: Time Trends In Proceduressupporting
confidence: 92%
“…Schizophrenia is associated with higher mortality rates than those in the general population mainly driven by natural causes of death, including acute coronary syn-drome (ACS) [1][2][3][4]. Hypotheses regarding the causal factors resulting in the increased mortality are many, nonetheless data support an increased prevalence of cardiac risk factors, metabolic side effects following the use of antipsychotic medication, as well as a decreased awareness or ability to describe symptoms in patients and a potential bias towards the patient from professionals [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…have concluded that patients with schizophrenia receive suboptimal preventive and cardiac care despite being at such high risk. [7][8][9][10] Furthermore, the use of atypical antipsychotic medications also contributes to the development of metabolic syndrome and consequently increases the risk of cardiovascular disease. 11 Despite the increased interest in this topic, there is a lack of comprehensive studies of the schizophrenia population with regards to comorbidities, in-hospital treatment, discharge medications and outcomes following AMI in contemporary nationwide study samples.…”
Section: Key Questionsmentioning
confidence: 99%
“… 5 6 Notably, several studies have concluded that patients with schizophrenia receive suboptimal preventive and cardiac care despite being at such high risk. 7–10 Furthermore, the use of atypical antipsychotic medications also contributes to the development of metabolic syndrome and consequently increases the risk of cardiovascular disease. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Social precipitants of early death are critical in this population: Poverty[ 154 ], homelessness[ 155 ], social isolation[ 156 ], poor hygiene[ 157 ], malnourishment[ 158 ], exposure to toxic substances[ 159 ] and adverse treatment effects[ 114 ]. High mortality from diabetes, cardiovascular disease and malignancies can, in part, be due to a relative lack of screening, delays in diagnosis, and suboptimal treatment[ 94 , 95 , 160 - 162 ]. Javatilleke et al[ 163 ] conclude their list of causes of lost life expectancy in severe mental illness by pointing out that the range of causes is very broad, with many putative causes varying according to gender.…”
Section: Physical Healthmentioning
confidence: 99%